Morphology and morphometric relationships of the sagitta of Diapterus auratus (Perciformes: Gerreidae) from Veracruz, Mexico - Rivera Félix, Verónica (2013)
Sagittae otoliths are the most studied because of their morphological variability and size; the sagittae may also have valuable taxonomic use and for D. auratus has not yet been described. In the present study we present a morphological description of the sagitta otolith and an analysis of its correlation with various morphometric parameters. The biological material was captured with a beach seine in the coasts of Alvarado and Port of Veracruz, from November 2009 to June 2010. Sagittae were extracted, cleaned, photographed (SEM and optical), and measured. The analysis included the correlations between sagitta’s length and width, versus the fish standard length, height and weight, for a total of 449 fishes. The comparison between left and right sagitta showed no significant difference in both otolith length and width (t-tests, p<0.05) for each sex. The right otolith was used for the correlations for both males and females and the Fisher test (d.f. 161 and 143, p<0.001) showed no significant differences in the slopes and intersections between them. The otolith length vs. fish weight correlation showed a positive allometric growth in males (b=3.9754, p<0.05) and females (b=4.3168, p<0.05).